Current scenario on illegal renovation in low-cost stratified properties in Klang valley and it impacts / Suraya Ghani - Ghani, Suraya (Faculty of Architecture, Planning and Surveying, 2013)
Illegal renovation as what it can be seen now a day had given so many impacts to the local authority and public too. Various method used by the responsible parties to overcome the issue but still exist. Hence, in this research the finding will be focused on the impacts gain by the local authority and the owners. Besides that, it also includes general information on data gain by visual observation survey conducted. Suitable recommendations also will be provided at end of this research. In order to gain the data and analyse the finding several methods will be used. The methodologies begins with understand the purpose of this research first, secondly establish the objectives. To answer the objectives books, internet, journal, by-law, visual observation, interview and questionnaire are used. Data gain then analyse before making the conclusion and came out with the recommendation. A complete report then produced. In the finding, summary of interview session made with local authority were provided together with analysis gain from distributed questionnaire given to local authority and the owner. In addition a record of visual building condition also provided as evidence of problems faced. This study discovers that owners of stratified property still do the illegal renovation on their strata units and give adverse impact to local environment